IMPROVEMENT OF MECHANISMS FOR IMPLEMENTING SCIENTIFIC RESEARCH RESULTS IN HIGHER EDUCATIONAL INSTITUTIONS (Universal International Scientific Journal, 2026)
This article discusses and analyzes the issues of improving the mechanisms for implementing scientific research results in higher education institutions. The theoretical foundations of scientific research and innovation activities are highlighted, and existing problems in the process of applying scientific developments created at universities to the production and social spheres are examined. Also, proposals and recommendations are developed to strengthen university-industry-state cooperation, develop innovative infrastructure, improve the process of commercializing scientific results, and introduce effective management mechanisms. The results of the study will help increase the efficiency of the innovation process in the higher education system.
Keywords: innovation; scientific research; implementation